Country’s Welfare as an Efficiency Factor in Fiscal Policy Promoting Economig Growth - Ushakov Denis; Natalia Bandurina; Sergey Shkodinsky (Montenegrin Journal of Economics, 2017)
The main problem of this study is an assessment of the current role of national tax regime in overcoming an injustice of national profit distribution, as well as in economic development stimulating in poor and wealthy countries. In this article the authors study the correlation between the dynamics of taxation regimes’ components and the macroeconomic indices of the countries’ worldwide so that to classify the countries into groups depending on the level of their welfare. Therefore, the article presents the authors’ conclusions concerning the efficiency of fiscal instruments for economic growth stimulation and external trade attractiveness increase as applied to the majority of contemporary states. Research proved a taxation effect in countries’ macro-economic growth and external attractive-ness stimulating, as well as this effect dependence on the level of countries material well-being and infrastructural conditions